Peningkatan pengetahuan masyarakat terkait dengan perilaku hidup bersih dan sehat (PHBS) untuk pencegahan stunting - Rohmah, Nur; Pratiwi, Fennysa Indrilla; Salsabila, Ashila; Asrianah, Asrianah; Rahmawati, Cica; Anggraini, Devica Novia; Haris, Ahmad; Tupa, Hildayani Kurlim; Nabila, Resha Rizqy; Rismayuti, Salsabila Dwi Aulia; Agustini, Rina Tri (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
The prevalence of stunting toddlers in East Kalimantan based on the national stunting prevalence is at 37.2%. East Kalimantan has a proportion of stunting toddlers in 2021 of 26.7%, and which are classified as short about 18.3% and also are very short about 8.4%. This community development aims to improve PHBS as a solution to health problems related to stunting issues, plan and implement intervention programs to prevent stunting in the RT 03 and RT 07 work areas, Rawa Makmur Village, Palaran District, Samarinda City. This activity was carried out using the theory of Dignan and Carr with the CARL method. The results of the activity obtained the problem of Clean and Healthy Living Behavior as an issue of stunting problems in the target area. The results of this activity have been carried out 2 intervention programs in the RT 03 and RT 07 Rawa Makmur areas which are indicators of PHBS including training on breastfeeding and MP-ASI as well as eating fruits and vegetables, and training on washing hands with soap. The conclusion of this activities is increasing significantly of the knowledge mean after the training (p value 0,001). Sustainability programs are needed to increase behavioral determinants related to reducing the risk of stunting.